Práticas pedagógicas em arte com crianças numa Escola do Campo: um estudo de caso no Povoado Folha Grossa - TO - Brito, Josivânia Ferreira (Universidade Federal do Tocantins, 2024)
It presents as main objective to identify how the pedagogical practice (s) of the art teacher is developed in the 1st grade class of the Elementary School of the Manoel de Sousa Lima Municipal School in the Folha Grossa Village, Tocantinópolis-TO. As specific, I highlight: to analyze how art teaching occurs in the 1st grade class of Elementary School of the Manoel de Sousa Lima Municipal School in the Folha Grossa/Tocantins; to reflect the theoretical and practical activities developed by students in the field of art in the rural school; check which methodologies are used by the teacher in art classes; understand how art is designed by the school's discipline teacher and political pedagogical project. As methodological procedures the research had qualitative approach of characteristic case study. The data collected in the research were generated from semistructured interviews with the teacher of the studied class and through the direct observations of the classes of Art of that same class. Among some results, I found in the research that the 1st year students had difficulty accompanying the teacher in most of the activities developed with the children, because they are students who are starting to become literate the contents exposed could be more worked for the year since most of the time only the following year of the observation group was able to follow and understand the content. Multiservice education is a great challenge for educators in this area, as they need to educate children of different levels of education and age. As this research shows, the educator makes his students understand the same subject, seeking to give relevance to the different age groups of the children. The progress and difficulties in a room must be evaluated in order to rethink its methodology. For this, it is necessary for this teaching of multiseriado classes that the policies of formation will be extended so that a higher education for the educators of the countryside is granted, so as to guarantee a qualified work for those who already work in the Field or for those who belong to the countryside and want to act in that space. In addition, the pedagogical practices with the researched class are developed through painting, sculpture, text systematization and practical classes, where the educator seeks to pass on to his students in a way only proposing no other teaching strategy if some student has not been able to conclude the methodology used.